FORMING A SENSE OF RESPONSIBILITY IN A PERSON DURING THE ACTIVITY - N. Raimov (Journals Park Publishing, 2022)
The article deals with theoretical research and analysis of the works of scientists and psychologists on the concept of responsibility as an important feature in the personality factor, personal and professional qualities of personality development, as well as on social responsibility and its significance in the educational activities of students.
Keywords: responsibility, social responsibility, norm, sanction, characteristics of students, volitional qualities